Penerapan Gaya dan Pendekatan Kepemimpinan untuk Kepemimpinan yang Efektif - Mansyur Hidayat Pasaribu (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this studi aimed to look at leadership styles and approaches to achieve effective leadership. This research is qualitative with a case study method. The results showed that there were several approaches to leadership, namely, a) approaches to leadership traits; b) behavioral approach to leadership, contingency approach to leadership; c) behavioral approach. In conclusion, the success of leadership is essentially related to the level of concern of a leader involved in two orientations, namely, the results that have been achieved by the organization (organizational achievement) and fostering of the organization (organizational maintenance). Several important factors can affect leadership effectiveness, namely the right perception, maturity level, proper assessment of the task, background and experience, expectations and leadership style, and professional relationships. The effectiveness of leadership also depends on the pattern of relationships constructed by the leader. Keywords: Leadership Style, Effective Leadership, Leadership Approach